فعالية مركب اللاميفودين في معالجة التهاب الكبدالمزمن الفعال B - السكيف, نضال علي (Latakia University Journal -Medical Sciences Series, 2019)
التهاب الكبد المزمن B مرض شائع عالمياً. ويأتي خطر المرض من تطوره نحو التشمع والتسرطن مسببا نسبة لابأس بها من الوفيات ومحملاً نفقات كبيرة في المعالجة على الصحة العامة. في السنين الأخيرة أظهر مركب Lamivudine فعالية في معالجة التهاب الكبد المزمن الفعال مع تحمل جيد للعقار وسهولة تناوله عن طريق الفم. أجريت الدراسة في مشفى الأسد الجامعي باللاذقية وفي وحدة أمراض جهاز الهضم التابعة لجامعة تشرين مابين تموز 2001 وأيار 2003 وشملت 24 مريضا أثبتت الدراسة السريرية والمخبرية وخزعة الكبد وجود التهاب كبد مزمن فعال لديهم بعد أن استبعد من الدراسة المرضى المعالجين سابقاً بالأنتيرفرون والحوامل والمرضعات ومن لديهم وجود علامات قصور في الوظيفة الكبدية. أعطي الجميع جرعة mg 100 من اللاميفودين لمدة سنة وتوبعوا خلال العام بإجراء فحوص مخبرية وخزعة الكبد في آخر المعالجة. التحسن على المعالجة قيم بسلبية HBV. DNA وتراجع قيم ALT ووجود أكثر من علامتين تدل على التحسن في دراسة الخزعة الكبدية بعد سنة حيث انخفضت قيم HBVDNA عند الغالبية العظمى 95% وعادت قيم ALT طبيعية عند 14 مريضا 58 % فقط خمسة مرضى أي 21% تحول HBeAg إلى سلبي مع ظهور أضداد anti bodies Hbe . بعض الأعراض الجانبية ظهرت أثناء المعالجة لكنها كانت محمولة وشملت التعب والإنهاك, الصداع, الغثيان, الإقياء, الآلام البطنية والإسهال. إن نتائج الدراسة تشير إلى فعالية مركب Lamivudine في معالجة التهاب الكبد المزمن الفعال. Chronic hepatitis B is a common disease all over the world. Its seriousness arises out of its ability to develop into cirrhosis and into cancer, causing a considerable rate of deaths, and increasing the expenses of the treatment which burdens the public health. In recent years" Lamivudine" showed high efficiency in treating chronic active hepatitis B and patients can take it by the mouth without difficulty. The study was done in AI-Assad university Hospital in the department of digestive system diseases which is a branch of Tishreen University between June, 2001 and May, 2003. The study included twenty four /24/ patients. The clinical, laboratory and hepatic biobsy studies have proved the existence of effective chronic hepatitis, after we excluded the patients who were earlier treated by interferon, pregnant women, feeding mother who have signs of failure of hepatic function . All patients were given a 100 mg dose of lamivudine for about a year and they were checked up during this year by making laboratory examinations and hepatic biopsy at the end of the treatment. Improvement after treatment was evaluated according to negative HBV. DNA and the decrease of AL T values. and the existence of more than two signs which indicate improvement in the study of hepatic biopsy after one year. Here we noticed that HBV/DNA values decreased in the great majority of patients (95%) and AL T values returned to normal state in fourteen patients (58%).with only five patients that is 21 % had changed HBeAg changed into negative with the appearance of antibodies HBe. Some side effects appeared during the treatment but they weren't so serious . These included exhaustion, headache, tiredness, nausea vomiting, Diarrhea and abdominal pains. The results of this study point out the effectiveness of Lamivudine in treating chronic active hepatitis B .